The association of firearm laws with firearm outcomes among children and adolescents: a scoping review - Zeoli, April M.; Goldstick, Jason; Mauri, Amanda; Wallin, Mikaela; Goyal, Monika; Cunningham, Rebecca (Journal of behavioral medicine, 2019)
We conducted a scoping review to determine the current state of knowledge and areas for advancements in research on the association of firearm laws with child and adolescent firearm-related outcomes. We queried Scopus, EMBASE, Pubmed, and CJ Abstracts for English language original empirical research articles on policies affecting child and adolescent firearm-related outcomes published between January 1, 1985 and July 1, 2018. Data were abstracted, and methodologic quality assessed. Twenty articles met inclusion criteria. Among the policies studied were child access prevention laws (12 studies) and minimum age restrictions for firearm purchase and possession (4 studies). Outside of child access prevention laws, which are associated with reductions in child and adolescent unintentional and firearm suicide deaths, there is, at best, equivocal evidence of policy effects. This area is understudied, particularly in regard to nonfatal firearm injuries, for which the lack of a national surveillance system hampers research efforts. Further rigorous firearm policy evaluations are needed.